2014
DOI: 10.1159/000371593
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Cognitive Load, Dementia and Hearing Loss

Abstract: Sensorineural systems play a crucial role in the diagnosis, treatment and management of several neurological disorders. The function of the eye and ear represents a unique window for testing various conditions in cognitive decline or dementia. Touch and smell have also been found to be strongly involved in neurodegenerative conditions, and their decline has been significantly associated with the progression of the disease; hence, the idea that restoring sensory function in cognitively impaired adults might ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 41 publications
2
83
0
2
Order By: Relevance
“…Especially in seniors, CIs become more important to enable better speech understanding and to include them therewith in the social environment 25 . It is also discussed whether better hearing can diminish dementia 26,27 . Beside improvement of speech understanding and therefore communication, the balance system plays an important role in the rehabilitation especially of older patients [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in seniors, CIs become more important to enable better speech understanding and to include them therewith in the social environment 25 . It is also discussed whether better hearing can diminish dementia 26,27 . Beside improvement of speech understanding and therefore communication, the balance system plays an important role in the rehabilitation especially of older patients [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…It is also discussed whether better hearing can diminish dementia 26,27 . Beside improvement of speech understanding and therefore communication, the balance system plays an important role in the rehabilitation especially of older patients [27][28][29] . Because the inner ear function includes also the labyrinthine, this has to be observed carefully while defining the indication to CI surgery and has to be monitored after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing impairment is the most common sensory deficit with prevalence reported to be as high as 64.1% in the population age above 65 years old[5, 6]. Since Uhlmann et al promoted a hypothesis that a relationship exists between hearing impairment and Alzheimer’s type dementia in the elderly[7], multiple sources have demonstrated a clear association between these two conditions[1, 6, 8-11].…”
Section: Hearing Lossmentioning
confidence: 99%
“…Several studies have confirmed the correlation between hearing loss and cognitive decline [Lin, 2011;Lin et al, 2011aLin et al, , b, 2013Lin et al, , 2014, and it has become increasingly evident that even very old people can benefit from procedures, such as cochlear implantation, that previously were recommended mainly for younger hearing-impaired patients [Castiglione et al, 2015;Ciorba et al, 2012]. Growing interest has been spreading in the scientific community for the potential to influence cognitive function, focusing on the possible role of auditory rehabilitation through digital devices in counteracting dementia [Fattahi et al, 2015;Martini et al, 2014;Mosnier et al, 2015]. The restoration of sensory functions among hearing-impaired older adults may allow for significant positive effects in their cognitive status.…”
Section: Introductionmentioning
confidence: 99%